Trichogramma pretiosum (Hymenoptera: Trichogrammatidae): Parasitismo natural em broca-pequena-do-tomateiro e dispersão em repolho, pepino e milho verde - Oliveira, Ruan Carlos de Mesquita (2017)
Parasitoids of eggs of the Trichogrammatidae family are the most commonly used and used natural enemies in the world in biological control programs applied for the control of lepidopteran pests. The objective of this study was to identify species/strains of Trichogramma spp. (Hymenoptera: Trichogrammatidae) collected in the Region of “Serra da Ibiapaba” Ceará State in Neoleucinodes elegantalis (Lepidoptera: Crambidae) eggs, already adapted to the environmental conditions, to determine the dispersion capacity of this parasitoid in cabbage crops, cucumber staked and of green corn in the Ceará State, Brazil. Eggs of N. elegantalis were collected in areas of conventional and organic tomato production and these emerged parasitoids identified by Trichogramma pretiosum (Hymenoptera: Trichogrammatidae). To determine a dispersion capacity of T. pretiosum collected with four distinct areas cultivated with staked cucumber, cabbage and corn in V4 and V8 stages. Unexplained eggs of Anagasta kuehniella (Lepidoptera: Pyralidae) were distributed in concentric circles of 2.5; 5.0; 9.0 and 12.0m. At the center of the circles 5,000 parasitoids were released. Females of T. pretiosum parasitized A. kuehniella eggs up to 12 m from the point of release. The mean dispersion distance of the V4 maize crop was 4.7 m with a dispersion area of 48.57 m² and a parasitism index of 18.36%, requiring 206 points/ha for releases of T. pretiosum. In maize in V8 stage the mean distance of 5.9 m, dispersion area of 60.27 m², average parasitism index 22.71% and 166 release points/ha. For a culture of cucumber staked at a mean distance of 6.0 m, dispersion area 62.20 m² with expected average parasitism of 21.08% and 161 release points/ha. For cabbage the mean distance of 5.59 m, dispersion area of 56.85 m² with expected average parasitism of 22.13% and 176 release points/ha.